Inducible chemical defenses in wild mungbean confer resistance to Spodoptera litura and possibly at the expense of drought tolerance - Yi-Ju, Chen; Boon Huat, Cheah; Chih-Yu, Lin; Yu-Ting, Ku; Cheng-Hsiang, Kuo; Yuan-Yun, Zhang; Bing-Rong, Chen; Nean Todaplou, Nina Olga; Cheng-Han, Hsieh; Pein-Min, Yeh; Freddy Kuok San, Yeo; Ya-Ping, Lin; et al. (Elsevier Science, Ltd., 2023)
Mungbean (Vigna radiata) is susceptible to many insect pests, but genotypes resistant to the common cutworm (Spodoptera litura) have yet to be identified. We screened for natural variants among wild mungbean populations and identified resistant (R1) and susceptible (S1) accessions. RNA-Seq data from R1 leaves exposed to larval feeding for 0, 2, 6 and 24 h suggested the involvement of CaMK, MAPK and jasmonic acid (JA) signaling, which diverts resources from primary metabolism to the biosynthesis of defense-related proteins and secondary metabolites. We compared the temporal expression of candidate genes in R1 and S1 plants exposed to larval feeding and observed the stronger induction of CAMK, MAPK, JA signaling, terpene and flavonoid biosynthesis genes in R1 plants. Accordingly, higher levels of JA accumulated in R1 leaves after larval feeding for 24 h, and metabolic profiling revealed elevated levels of tryptophan and tyrosine in R1 plants, possibly triggering the accumulation of glucosylated kaempferols and the emission of the volatile (E)-β-ocimene. Drought stress experiments showed that the inducible chemical defense system in accession R1 may come at the expense of drought tolerance. This potential trade-off between abiotic and biotic stress tolerance may reflect the lower levels of endogenous proline in R1 plants.